Aktivitas Antioksidan Umbi Bawang Dayak (Eleutherine bulbosa) Yang Diberi Pupuk Kompos Cair Daun Paitan (Thitonia diversifolia) Hasil Fermentasi Ragi Tape - Fita Afifaturrosydah; Tatang Sopandi; Vivin Andriani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2022)
Dayak onion (Elrutherine bulbosa) is a plant that is efficacious for treating various health problems because it is known to contain secondary metabolites flavonoids that function as antioxidants. However, synthesis and antioxidant activity of secondary metabolites flavonoids and non-flavonoids are influenced by fertilization. This study aims to test the antioxidant activity of Dayak onion tubers which are given the liquid compost of the fermented tape. The study was conducted experimental using a complete random experimental design 4 Treatment for the concentration of Paitu Yaotu leaf fertilizer 10%, 20%, 30%, and 40%. Giving water distilata and NPK fertilizer (16:16:16) is used as a negative and positive control. The results showed that the fertilization of the liquid compost of the fermented leaf fermented tape had a significant effect (p <0.05) on the antioxidant activity of Dayak onion tubers. Giving with a concentration of 20% is the optimal concentration of compost liquid fertilizer with ferrmed tape yeast with IC50 value 86.01 μg/ml. Keywords: fertilizer, paitan plant leaves, tape yeast, dayak onion plant